Assessment of a Novel Standardized Training System for Mandibular Contour Surgeries - Qiao, Jia (JAMA Facial Plast Surg, 2019)
IMPORTANCE: Mandibular contour surgeries (MCS) involving reduction gonioplasty and genioplasty are rewarding for patients with square faces; however, the procedure has inherently difficult clinician learning curves and unpredictable skill acquisitions. To our knowledge, there has been no effective, validated training model that might improve training and surgical outcomes for MCS. OBJECTIVE: To establish and evaluate a standardized intraoral MCS training system. DESIGN, SETTING, AND PARTICIPANTS: Intraoral MCS training models were constructed by 3-dimensional (3D) skull models covered with elastic head cloths. From April 2016 to April 2018, 90 consecutive MCS patients (30 per group) and 15 craniofacial surgery fellow physicians (5 per group) were enrolled in the prospective observational study. They were randomly divided into intervention groups (A and B) and a control group (C). Intervention groups A and B completed 5 training sessions on the intraoral MCS training models before each clinical case. Group A performed both the model training sessions and clinical surgeries with surgical templates. Control group C had no extra training before clinical surgeries. All groups completed clinical surgery under supervision on 6 patients. The duration of follow-up was at least 3 months postoperatively. INTERVENTIONS: Intraoral MCS training models were provided to intervention groups (A and B) before clinical surgeries. Surgical templates were provided to intervention group A both in training sessions and clinical surgeries. MAIN OUTCOMES AND MEASURES: The completion time, surgical accuracy, learning curves, operating confidence, surgical skill, and outcome satisfaction of each procedure were recorded and analyzed with paired t test and 1-way analysis of variance test by blinded observers. RESULTS: All 90 patients (14 men, 76 women; mean [SD] age, 26 [5] years) were satisfied with their postoperative mandible contours. The intervention groups (A and B), especially the group with surgical templates (A) showed improvements in clinical surgery time (mean [SD], group A 147.2 [24.71] min; group B, 184.47 [16.28] min; group C, 219.3 [35.3] min; P = .001), surgical accuracy (mean [SD], group A, 0.68 [0.22] mm; group B, 1.22 [0.38] mm; group C, 1.88 [0.54] mm; P < .001), learning curves, and operators' confidence and surgical skill. CONCLUSIONS AND RELEVANCE: The intraoral MCS training model was effective and practical. The optimal intraoral MCS training system included intraoral MCS training models and surgical templates. The system significantly decreased clinical surgery time, improved surgical accuracy, shortened the learning curve, boosted operators' confidence, and was associated with better acquisition of surgical skills. LEVEL OF EVIDENCE: NA.